2021
DOI: 10.3389/fphar.2021.656561
|View full text |Cite
|
Sign up to set email alerts
|

The CNS-Penetrant Soluble Guanylate Cyclase Stimulator CY6463 Reveals its Therapeutic Potential in Neurodegenerative Diseases

Abstract: Effective treatments for neurodegenerative diseases remain elusive and are critically needed since the burden of these diseases increases across an aging global population. Nitric oxide (NO) is a gasotransmitter that binds to soluble guanylate cyclase (sGC) to produce cyclic guanosine monophosphate (cGMP). Impairment of this pathway has been demonstrated in neurodegenerative diseases. Normalizing deficient NO-cGMP signaling could address multiple pathophysiological features of neurodegenerative diseases. sGC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 66 publications
2
36
2
Order By: Relevance
“…Similar to our study, vericiguat reduced MAP, albeit in a 10x higher dose-range. The effective vericiguat doses in the study by Correia et al [69] are significantly higher than our memory-enhancing effective dose of 0.3 mg/kg. However, the differences between the brain-penetrant sGC stimulator CY6463 and the non-penetrant sGC stimulator vericiguat suggest mechanistically different pathways in memory enhancement.…”
Section: Alternative Effectscontrasting
confidence: 73%
See 1 more Smart Citation
“…Similar to our study, vericiguat reduced MAP, albeit in a 10x higher dose-range. The effective vericiguat doses in the study by Correia et al [69] are significantly higher than our memory-enhancing effective dose of 0.3 mg/kg. However, the differences between the brain-penetrant sGC stimulator CY6463 and the non-penetrant sGC stimulator vericiguat suggest mechanistically different pathways in memory enhancement.…”
Section: Alternative Effectscontrasting
confidence: 73%
“…However, it is likely that its very narrow therapeutic window on cognition could also play a role, i.e., the optimum dose for a (likely peripheral) effect was missed. Interestingly, in a recent study Correia et al [69] compared the novel brain penetrant sGC stimulator CY6463 to vericiguat and discovered that vericiguat did not increase cGMP levels in the CSF of rats after oral dosing with 30 mg/kg. In addition, altered fMRI-BOLD signals were found in only peripheral cortical regions after intravenous infusion of 3 mg/kg.…”
Section: Alternative Effectsmentioning
confidence: 99%
“…In rats, CYR119 increased cGMP levels in CSF after oral dosing, consistent with results from preclinical studies of the clinical-stage CNS-penetrant sGC stimulator CY6463, which also demonstrated an increased in CSF cGMP. The ability of CNS-penetrant sGC stimulators to increase cGMP levels in the CSF is in contrast to that of CNS-restricted sGC stimulators that do not alter CSF cGMP levels [ 9 ]. Consistent with previous work showing that increased NO–sGC signaling can modulate inflammation [ 18 , 23 ], we found that CYR119 reduced the LPS-induced inflammatory response in cultured microglial cells, reduced QA-induced neuroinflammation in rats [ 15 ], and reduced inflammatory gene expression in a DIO mouse model that is an established model of neuroinflammation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous work showing that in a mouse model of cerebral malaria, treatment with an NO-donor decreased expression of ICAM-1 and P-selectin in the brain [ 31 ]. Future work with CYR119 or another CNS-penetrant sGC stimulator such as CY6463 [ 9 ] in additional models with more pronounced cytokine expression will increase the understanding of the role of the NO–sGC–cGMP pathway in neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation